2021
DOI: 10.3389/fcvm.2021.773200
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Index Improves the GRACE Score Prediction of Clinical Outcomes in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Background: Malnutrition has been shown to be associated with adverse cardiovascular outcomes in many patient populations.Aims: To investigate the prognostic significance of malnutrition as defined by nutritional risk index (NRI) in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) and whether NRI could improve the GRACE score based prognostic models.Methods: This study applied NRI among 1,718 patients with ACS undergoing PCI. Patients were divided into three nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Malnutrition is a common risk factor for poor prognosis in various populations, whether assessed by subjective or objective tools or single biomarkers. [ 5 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] Our findings confirmed its prognostic significance in patients with CAD and coexisting abnormal glycemic status. Notably, we presented a novel finding that the malnutrition-related risk for all-cause death and MACCE outweighed the diabetes-related risk.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Malnutrition is a common risk factor for poor prognosis in various populations, whether assessed by subjective or objective tools or single biomarkers. [ 5 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] Our findings confirmed its prognostic significance in patients with CAD and coexisting abnormal glycemic status. Notably, we presented a novel finding that the malnutrition-related risk for all-cause death and MACCE outweighed the diabetes-related risk.…”
Section: Discussionsupporting
confidence: 78%
“…The diabetes group comprised more malnourished patients than the prediabetes group, which may have resulted from increased protein catabolism, decreased protein anabolism, elevated urinary protein excretion, and probably, inadequate protein intake in the setting of diabetes. Prior small-scale research has investigated malnutrition in older patients with diabetes [ 16 , 17 , 19 ] and patients with ACS [ 5 , 8 , 14 , 15 ], respectively, and may not have been epidemiologically representative of the general population with abnormal glycemic status and CAD. Only one study [ 13 ] reported malnutrition in CAD patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have identified some potential risk factors combined with the GRACE score, which attempted to enhance the predictive ability for adverse clinical outcomes after ACS, such as nutritional risk index [ 25 ], neutrophil count [ 26 ], B-type natriuretic peptide [ 27 ], 2-hour postload glucose [ 28 ], and hemoglobin A1c [ 23 ]. The populations enrolled in the above studies were patients with STEMI or nondiabetic patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that the strong and effective prognostic value of the GRACE score has been confirmed by much evidence ( 3 , 4 , 19 21 ), early risk stratification remains urgently needed for further optimization, especially for low-risk patients with ACS. Therefore, previous studies have recently explored ways to improve the predictability of the prognostic GRACE score, including adding NT-pro-BNP ( 22 ), 2-h postload plasma glucose ( 23 ), plasma glucose blood inflammation-related indicators ( 24 ), plasma myeloperoxidase and trimethylamine N-oxide ( 25 ), serum acid uric acid ( 26 ) and nutritional risk index ( 27 ) to the GRACE score. The findings indicate that blood biochemical indexes and biomarkers provide incremental prognostic information for the predictive capacity of the GRACE score-based prognostic models.…”
Section: Discussionmentioning
confidence: 99%